School Management Policy in Determining Vocational Competency Test Schemes for Vocational Education - Sayuti, Muhammad; Nur Setyanto, Barry; Kunta Biddinika, Muhammad; Mulyani, Sri; Khoirul Ma’arif, Muhammad; Suwardi, Suwardi; Harinto, Joko; Wijantoro, Fuad; Agus Susanto, Harry; Hasanah, Noviatun; Chuma Opwora, Meshack (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: Vocational education plays a strategic role in preparing competent workers aligned with industrial needs, yet the implementation of the Skills Competency Test (UKK) still faces issues such as gaps between taught competencies and industry demands, mismatches between education and the labor market, and the lack of UKK standardization. This study aims to analyze vocational school policies in designing UKK schemes to enhance the relevance of vocational education to labor market needs, focusing on the effectiveness of these policies in preparing students to face workplace challenges. Method: The research method is carried out through case studies with the stages of formulating research focus, data collection, data processing and analysis, triangulation of findings, and drawing conclusions as a basis for recommendations for improving the vocational education system. Results indicate UKK scheme selection relies on internal and external factors, particularly industry synchronization. The industrial scheme is more technologically adaptive and cost-efficient than LSP. However, trade-offs include limited facilities and the short three-year LSP certificate validity relative to industry demands. Periodic evaluation of materials and tools is essential to address gaps, enhance quality, and prepare graduates for global competition. Novelty: Going beyond procedural compliance, this study offers new insights into UKK standardization by analyzing strategic scheme selection. This study integrates policy analysis with implementation results to redefine UKK as a mechanism for operationalizing national standards and enhancing graduates' global competitiveness.